ROBAINOGNATHUS JENSENI ROMER, 1970 (REPTILIA, THERAPSIDA) DE LA FORMACION ISCHICHUCA (TRIASICO MEDIO), LA RIOJA, ARGENTINA (Ameghiniana, 2013)
The study of the endocraníal casts of cynodonts and Mesozoic mammals isclearly the unique way to know at least sorne of the events that have occurred in thebrain during tbe reptile-marnmal transition. Erobainognathus [enseni was a very advanced cynodont from the Míddle Triassic. The endocranial cast shows a great brain-like appearance. The cerebral hemispheres are long and narrow, and taper anteriorly. A slope on the caudal dorsal surface of the hemispheres probably indicates the caudal border of the developing neocortical plate. Tbe cerebellar regio n shows a consistent development and the tectum mesencephali appears to be reduced. All these features agree with the expected general morphology of the brain of an intermediate stage between reptiles and mammals. Moreover, the quantitative analysis suggests an i ntermediate relative braín size between the known data for certain reptiles and mammals. We arríved to the conclusion that Probainognathus is in an advanced stage towards the mammalian neurologic pattern.